Application of novel CAR technologies to improve treatment of autoimmune disease - Cheever, Abigail; Kang, Chloe C.; O’Neill, Kim L.; Weber, K. Scott (Frontiers in Immunology, 2024)
Chimeric antigen receptor (CAR) T cell therapy has become an important treatment for hematological cancers, and its success has spurred research into CAR T cell therapies for other diseases, including solid tumor cancers and autoimmune diseases. Notably, the development of CARbased treatments for autoimmune diseases has shown great progress recently. Clinical trials for anti-CD19 and anti-BCMA CAR T cells in treating severe B cell-mediated autoimmune diseases, like systemic lupus erythematosus (SLE), have shown lasting remission thus far. CAR T cells targeting autoreactive T cells are beginning clinical trials for treating T cell mediated autoimmune diseases. Chimeric autoantigen receptor (CAAR) T cells specifically target and eliminate only autoreactive B cells, and they have shown promise in treating mucosal pemphigus vulgaris and MuSK myasthenia gravis. Regulatory CAR T cells have also been developed, which show potential in altering autoimmune affected areas by creating a protective barrier as well as helping decrease inflammation. These new treatments are only the beginning of potential CAR T cell applications in treating autoimmune disease. Novel CAR technologies have been developed that increase the safety, potency, specificity, and efficacy of CAR T cell therapy. Applying these novel modifications to autoimmune CARs has the potential to enhance the efficacy and applicability of CAR therapies to autoimmune disease. This review will detail several recently developed CAR technologies and discuss how their application to autoimmune disease will improve this emerging field. These include logic-gated CARs, soluble protein-secreting CARs, and modular CARs that enable CAR T cell therapies to be more specific, reach a wider span of target cells, be safer for patients, and give a more potent cytotoxic response. Applying these novel CAR technologies to the treatment of autoimmune diseases has the potential to revolutionize this growing application of CAR T cell therapies.